2022
DOI: 10.3390/horticulturae8040318
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Organic Fruit Consumer Behavior: A Systematic Review

Abstract: This review article seeks to systematically identify appropriate ways to measure the consumption behavior of organic fruits. The systematic review of the literature was performed according to the criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the eligibility criteria were declared through the PICOS (population, interventions, comparators, outcomes, and study) tool based on 277 article records scientiometrically identified in both the Journal Citation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Regarding the method for analysis, the data from the articles were collected through surveys or questionnaires that were statistically analyzed using several methods, including exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). In this way, it was possible to compare indicators through updated validity and reliability parameters used in other studies such as that of [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

How to Measure Management Skills: Systematic Review

Andino-González,
Vega-Muñoz,
Salazar-Sepúlveda
2024
Preprint
“…Regarding the method for analysis, the data from the articles were collected through surveys or questionnaires that were statistically analyzed using several methods, including exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). In this way, it was possible to compare indicators through updated validity and reliability parameters used in other studies such as that of [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline [25] and the PICOS (population, interventions, comparators, outcomes, and study) tool were used to establish eligibility criteria for articles [26,27] being also used by [28].…”
Section: Methodsmentioning
confidence: 99%

How to Measure Management Skills: Systematic Review

Andino-González,
Vega-Muñoz,
Salazar-Sepúlveda
2024
Preprint
“…Price is another important factor that consumers consider when buying organic products [ 76 ]. Likewise, it is observed that the attitude towards organic food is the main determinant of the purchase intention, and together with health concerns and the perception of quality, it has a significant impact on the access and consumption of organic products [ 77 ]. Therefore, this research exposes the factors that are linked to the behaviour and attitude of the consumer in the purchase of organic products; as evidenced in the case of culture and demographics, there is a non-significant relationship with behaviour [ 78 ], while within the attitude of the consumer during the purchase, elements such as motivation, feelings, and emotions are identified.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement instrument used was selected through a previous systematic review work [45], which has contrasted among 184 papers published in Web of Science the model proposed by Jose & Kuriakose [25] (See Appendix A), to provide validity and reliability in the measurement, surpassing in statistical terms other reviewed articles that measure the organic fruit consumer behavior [20,40,46]. Thus, the Jose & Kuriakose [25] scale integrates the constructs that allow studying this consumption behavior, proposed by Scarpa & Thiene [47] (fear), Steptoe et al [48] (health), Gil et al [49] (environmental motivations), Steptoe et al [48] (perceived price), Dickieson et al [50] and Lichtenstein & Burton [51] (purchase effort).…”
Section: Methodsmentioning
confidence: 99%